Kelelawar Pemakan Buah Sebagai Polinator yang Diidentifikasi Melalui Polen yang Digunakan Sebagai Sumber Pakannya di Kawasan Sektor Linggarjati, Taman Nasional Ciremai Jawa Barat - Maryati, Maryati; Kartono, Agus Priyono; Maryanto, Ibnu (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTPollinator Bat Identification Based on Pollen as Feed Resources at LinggarjatiDistrict-Ciremai National Park, West Jawa. Pollen identification that used for feedresources by six species of frugivorous bats from Ciremai National Park was identifiedunder microscope. The results shown that are known 21 species as important plants forbats and in the contrast possibly for bats as pollinator. By the principle componentanalysis and cluster grouping based on Euclidian distance indicated that Aethalops alecto,Chironax melanocephalus as important polinator role in primary forest and high in elevationlevel, C. brachyotis and Macroglossus sobrinus in secondary or fragmented forest andMegaerops kusnotoi in lower primary forest and Cynopterus tittacheilus is important rolefor intermediate area between primary and secondary forest and at lower elevation range.On the niche overlaps analysis indicated that the highest overlaps were known in C.brachyotis and M. sobrinus (0.881) but the lowest in niche overlaps between M. sobrinusand C. melanocephalus (0.288)Key words: pollen, bats, feed resources